PEMANFAATAN EKSTRAK BUAH Morus alba L. (Murbei) SEBAGAI PENGAWET ALAMI IKAN Selaroides leptolepis (Selar) - Diah Sari Nastiti; Nurhamidah Nurhamidah; I Nyoman Chandra (University of Bengkulu, 2019)
The purpose of this study is to measure the influence of concentration and time of soaking of fruit extracts Morus alba l. (Mulberry) is effective as a preservative Selaroides leptolepis fish (Trevally). Samples taken of coral in the fruit of the Holy City of Argamakmur, North Bengkulu and trevally fish samples taken directly from the beach, the village Plow Jakat, province of Bengkulu. Fruit samples grinded using a blender and aqueous extracts are obtained through maceration method using aquades and filtered so that retrieved the mulberry and subsequent solution diluted with aquades be a concentration of 20, 40, 60 and 80% (v/v). Phytochemicals profile test to determination of secondary metabolites in extracts. The test is done through the methods of preserving this soaking on a several concentrations variation and soaking time with without soaking as control. The variation of the concentrations is done at a concentration of 10, 20, 30 and 40%, with soaking time variation 1, 2 and 3 hours. Variation of time observations were at 12, 18 and 24 hours and test the chemical content in the form of a test of water content, levels of Total Volatile Bases (TVB), and pH values. Phytochemical test results obtained the presence of saponins, alkaloids, terpenoids, phenolic and flavonoid compounds and do not contain steroids. The results showed that the extract of Mulberry fruits proved capable of lowering the pH and the levels of TVB but does not affect the water content of the fish. Soaking time variations do not affect the water content, pH and the levels of TVB. From the results obtained that the use of the mulberry fruit extract at concentrations of 30% with long submergence 1 hour most optimal for use as a preservative natural for S. leptolepis up to 18 hours at room temperature to the value pH 6.7 and TVB at 27.2 mg N%.